Actual Optical and Thermal Performance of PV Modules - Krauter, Stefan; Hanitsch, Rolf (Solar Energy Materials and Solar Cells)

Actual Optical and Thermal Performance of PV Modules - Krauter, Stefan; Hanitsch, Rolf (Fuel and Energy Abstracts)

Sonneneinstrahlung - Krauter, Stefan (Solararchitektur für Europa, Hrsg.: A. Schneider; Basel, Boston, New York)

New Optical and Thermal Enhanced PV Modules Performing 12% better under True Module Rating Conditions - Krauter, Stefan; Hanitsch, Rolf; Moreira, L. (Proceedings of the 25th IEEE–PV–Specialists Conference, Washington D.C. (USA), 13.–19. Mai 1996, Band 1, S. 1323–1326.)

Lernen im Internet am Beispiel der Solarenergie - Krauter, Stefan (Bildung im Netz)

Graph Transformation for Specification and Programming - Andries, Marc; Engels, Gregor; Habel, Annegret; Hoffmann, Berthold; Kreowski, Hans-Jörg; Kuske, Sabine; Plump, Detlef; Schürr, Andy; Taentzer, Gabriele
The framework of graph transformation combines the potentials and advantages of both, graphs and rules, into a single computational paradigm. In this paper we survey recent developments in applying graph transformation as a rule-based framework for the specification and development of systems, languages, and tools. After presenting the basic features of graph transformation, we discuss a spectrum of applications including the evaluation of functional expressions, the specification of an interactive graphical tool, an example specification for abstract data types, and the definition of a visual database query language. The case studies indicate the need for a graph transformation language that provides suitable structuring principles and is independent of a particular graph transformation approach. To this end, we sketch the basic features of the new graph- and rule-centered language Grace, currently under development, that permits systematic and structured specification and programming based on graph transformation.

Definition of an Encapsulated Hierarchical Graph Data Model: Static Aspects, Part 1. - Busatto, Giorgio; Engels, Gregor

Object-oriented Specification of Coordinated Collaboration - Engels, Gregor; Groenewegen, Luuk; Kappel, Gerti

Horizontal and Vertical Structuring of Typed Graph Transformation Systems - Heckel, Reiko; Corradini, Andrea; Ehrig, Hartmut; Löwe, Michael

Towards Measurable Process Models - de Bunje, Tineke; Engels, Gregor; Groenewegen, Luuk; Heus, Michael; Matsinger, Aart (Proceedings of the Workshop on Software Process Technology (EWSPT 1996), Nancy (France))